PENGARUH THREE QUARTER BAFFLE TERHADAP LAJU PERPINDAHAN KALOR DAN DAYA POMPA PADA KONDENSOR VERTIKAL - Cahyo Wibi Yogiswara; Fauzun; Muhammad Salim Taufiqurrahman (Mechanical Engineering Department, Faculty of Engineering, Universitas Lambung Mangkurat, 2025)
A condenser is a heat exchanger that functions to convert vapor into liquid. One of the most commonly used of condensers is the shell and tube. This study was conducted on a laboratory-scale vertical condenser to determine the heat transfer coefficient, pressure drop, and the ratio of heat transfer rate to the required pump power. In this study, variations were made in four types of baffles and three mass flow rate ratios. The baffle types used include segmental, disc and doughnut, and three-quarter with 90° and 180° configurations. Meanwhile, the mass flow rate ratio was varied based on theoretical values, namely 90%, 100%, and 110% of the theoretical value. The condenser used is a shell and tube, where the hot fluid flows through the tube, and the cold fluid flows through the shell. Experimental results show that variations in baffle type and mass flow rate ratio significantly affect the heat transfer coefficient and the ratio of heat transfer rate to pump power. The three-quarter baffle with a 90° configuration demonstrated the best performance, with a heat transfer coefficient of 83.27 W/m²°C and a heat transfer rate-to-pump power ratio of 1.64 at a water flow rate of 2.2 GPM.